Reconstruction of Palaeo-hydrology and fluvial architecture at the Orosháza palaeo-channel of River Maros, Hungary - Katona, Orsolya; Sipos, György; Onaca, Alexandru; Ardelean, Florina (Journal of Environmental Geography, 2012)
Several studies have addressed the impact of climate change and tectonic activity on fluvial systems. When investigating these systems palaeo-hydrological and geomorphological data on abandoned channels can yield valuable results. The main aim of our work was to reconstruct morphological conditions at the Orosháza palaeo-channel and to estimate the bankfull discharge which characterized the channel during its formation. There are several equations predicting bankfull discharge on the basis of planform parameters, but these only work for meandering rivers. In case of braided channels flow reconstruction can only be made by using cross-sectional parameters. The Orosháza palaeo-channel provided the means of a comparative analysis in this respect. By a sudden pattern change both meandering and braided reaches, supposedly having a very similar bankfull discharge, could be simultaneously studied. Planform parameters and present cross-sections were determined on the basis of a high resolution DEM, while original cross-section parameters were assessed using sedimentological and geophysical methods. Based on sedimentological data, channel pattern transition was mainly driven by intensive bedload accumulation at the edge of the Maros Alluvial Fan (MAF). Slope differences could not be evened out due to an avulsion close to the apex of the fan. Concerning discharge calculations a good agreement was found between a region-specific planform based equation and the cross-section based Grauckler-Manning equation. Values determined for the braided and meandering reach were also in a good correspondence. Consequently, the presented approach is suitable to determine the discharge of other braided palaeo-channels on the MAF and elsewhere.